Professional Performance Obstacles of the Social Worker in the School Domain: A Field Study on Preparatory Schools in Tobruk City - الدمنهوري وائل صلاح (Tobruk University Journal of Social and Human Sciences, 2024)
The social service in the school’s field is defined as the professional practice of the methods and patterns of the social service in the educational institution with pupil / student on different aspects (as individual, member of group, family, school organizations, society) inside or outside the school including the programs and educational activities in cooperation with school system, aim of supporting the educational process and the proper upbringing in order to increase the rate of educational attainment. these efforts also help to develop the relationships and links between the parties of the education system which. Help to create the appropriate education climate improving the educational Process outcome discovering, developing the innovative and creative talents with helping all types of the students including outstanding, the disabled ones. And those who are stumbled in their education in order to achieve the teaching, educational, social and productive objectives for its children preparing for the future. from here it showed us the degree of importance the social worker’s role in the school field despite this importance but there many obstacles that hinder the professional performance of social worker in the school field there fore the current study sought to monitor these obstacles and identify their dimensions also the current study is considered as one of the descriptive ones that concerned monitoring the reality and identifying its dimensions. Whereas the researcher used the comprehensive survey through application of Questionnaire form directed to all social workers in the preparatory schools Of Tobruk city. the results of the study showed that there are many obstacles hindering the professional performance of social worker that can be summarized as follows: Assigning the social worker with administrative burdens out scope of his professional specialty.obstacles which are related to the school administration that is the permanent confusion between the social worker’s role and the psychologist role. Obstacles are related to lack of awareness of importance of the social Worker’s role. Obstacles which are related to the students that is fear of some students to reveal their secrets to the social worker Therefore, the current study recommended the importance of preparing programs to improve the efficiency of the social worker and organizing of awareness programs for all parties of the educational process about social service’s role, its goals and objectives.